Collaborative Reflection to Enhance Teachers’ Teaching Ability Utilized Inquiry Model - Richa Widya Tani; M. Jaya Adi Putra; Hendri Marhadi (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
This research aims to explore the prospective teachers activities to enhanceteachers’ teaching skills utilized inquiry by perform reflective collaborativeactivities between teachers, coaches and prospective teachers. Activitiesreflection helps prospective teachers make improvements in the implementationof tasks so that for further learning meetings prospective teachers can improveteaching skills. Improved teaching ability to give impact on teacher activities andstudents who experience improvement at each meeting so that it has aninfluence on student learning outcomes. In understanding the concept ofstudents' average heat energy increased from the average base score of 64.91 to76.22. In understanding the concept of average student sound energy from thebasic score to 81.72. The increase of learning result can be seen from theaverage of N-Gain on the understanding of the concept of heat energy of 0.32medium categories and on the understanding of energy concept of 0.47 mediumcategories. This study concluded that the application of inquiry learning modelcan improve science learning outcomes based on reflection by prospectiveteachers.